CONSERVATION PARTNERSHIP POLICY IN SUSTAINABLE DEVELOPMENT IN THE FORESTRY SECTOR - Djuariah; Andri, Gusti Yosi; Sutrisno, Endang (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2024)
The impact of changing the status of the protected forest on Mount Ciremai into a national park is felt to be very detrimental to the surrounding community because they no longer utilize the natural resources in the forest freely. Nature lovers and activists welcome this status change because it will better preserve the ecosystem and habitat in forest areas. Mount Ciremai National Park (MCNP) has received several proposals from local communities to utilize the area around the forest. However, a decision has yet to be made because it considers regulations and policies so it does not conflict with legal provisions. This research analyzes the policy provisions for using forest areas that have changed to national parks, which can no longer be used in the business sector. The research method uses a normative juridical method, considering that the activities revolve around reviewing policies in the form of regulations and laws. The research results show that the conservation partnership model is intended for local communities who depend on natural resources in the MCNP area for their livelihoods. The concept of Adaptive Collaboration Management (ACM) is applied in this conservation partnership so that the community and its facilities can pick up or collect non-timber products (NTPs) and non-timber forest products (NTFPs) both outside and inside the forest area while maintaining the sustainability of the forest ecosystem so that future generations can utilize it.